Surface State‐Mediated Charge Transfer of Cs2SnI6 and Its Application in Dye‐Sensitized Solar Cells. Issue 3 (30th November 2018) - Shin, HyeonOh; Kim, Byung‐Man; Jang, Taehyung; Kim, Kwang Min; Roh, Deok‐Ho; Nam, Jung Seung; Kim, Jeong Soo; Kim, Un‐Young; Lee, Byunghong; Pang, Yoonsoo; Kwon, Tae‐Hyuk
Abstract: A vacancy‐ordered double perovskite, Cs2 SnI6, has emerged as a promising lead‐free perovskite in the optoelectronic field. However, the charge transfer kinetics mediated by its surface state remains unclear. Here, the charge transfer mechanism of Cs2 SnI6 is reported and the role of its surface state in the presence of a redox mediator is clarified. Specifically, charge transfer through the surface state of Cs2 SnI6 and its subsequent surface state charging are demonstrated by cyclic voltammetry and Mott–Schottky measurements, respectively. Because it is expected that the surface state of Cs2 SnI6 is capable of regenerating oxidized organic dyes, a Cs2 SnI6 ‐based regenerator is developed for a dye‐sensitized solar cell composed of fluorine‐doped tin oxide (FTO)/dyed mesoporous TiO2 /regenerator/poly(3, 4‐ethylenedioxythiophene)/FTO. As expected, the performance of the Cs2 SnI6 ‐based regenerator is strongly dependent on the highest occupied molecular orbital of the dyes. Consequently, Cs2 SnI6 shows efficient charge transfer with a thermodynamically favorable charge acceptor level, achieving a 79% enhancement in the photocurrent density (14.1 mA cm −2 ) compared with that of a conventional liquid electrolyte (7.9 mA cm −2 ). The results suggest that the surface state of Cs2 SnI6 is the main charge transfer pathway in the presence of a redox mediator and should be considered in future designs of Cs2 SnI6 ‐based devices. Abstract : The surface state belonging to the bandgap of Cs2 SnI6 is observed as the main charge transfer route in Cs2 SnI6 with redox mediators, and the surface state‐mediated charge transfer of Cs2 SnI6 is utilized as a charge regeneration in dye‐sensitized solar cells.